Peran Orientasi Wirausaha dalam Meningkatkan Kinerja Pemasaran dengan Kapabilitas Inovasi sebagai Mediasi - Tatang Rois; Suliyanto Suliyanto; Lusi Suwandari (Universitas Kuningan, 2023)
This research was conducted to explain the differences in the results of research on the effect of entrepreneurial orientation on marketing performance by adding innovation capability as a mediating variable. This research method uses quantitative methods with the object of this research being SMEs in Kuningan Regency. The sampling technique used is random sampling method with a sample size of 100 respondents. This study uses a regression analysis tool with a product of coefficients in facilitating testing of mediating variables. Based on the results of hypothesis testing, it is known that all of them are supported by a significance level that meets the specified requirements.